(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
The incidence of club foot is 4 to 6 per 1000 births and majority of the babies with club foot are born in the developing countries.1Multiple factors are responsible for this deformity. The vascularity and the accessory muscles of the feet also have an important role to play.2,3 We also know that there is an abundance of collagen in the ligaments which are stretchable but the collagen in Tendoachillis is not stretchable therefore, Tenotomy has to be done.4 Out of many classifications of club foot, Pirani classification and the Dimeglio classification are accepted all over the world today.5 The radiography in club foot has many pitfalls6,7 whereas, the ultrasonography shows significant correlation as the non ossified Talar bones can also seen.8 The computerized pedobarography although popular in some centers also does not correlate with the clinical outcome.9 Even today the treatment of this deformity although looks simple is still challenging as it has high rate of recurrence in some countries.